2022
DOI: 10.3389/fmicb.2022.1033875
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides alleviates lipopolysaccharides-induced inflammatory lung injury by altering intestinal microbiota in mice

Abstract: Inflammatory lung injury is a common respiratory disease with limited therapeutic effects. Increasing opinions approved that prevention is more important than drug treatment for inflammatory lung injury. Astragalus polysaccharides (APS) has multiple bioactivities including anti-inflammation and immunoregulation. However, its preventive effects on inflammatory lung injury remain unclear. In this study, mice were pretreated with APS via intragastric gavage and then were intratracheally instilled with lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Several studies have shown that traditional Chinese medicines have antiviral and immune-enhancing effects ( 29 ). RH is used to treat various immune diseases, such as tumours, asthma, and rheumatoid arthritis ( 21 ), although the medicinal value of these active ingredients has rarely been reported ( 30 ). SG is the dried S. scutellariae root from which baicalin is extracted from the by-product of Scutellaria flavones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that traditional Chinese medicines have antiviral and immune-enhancing effects ( 29 ). RH is used to treat various immune diseases, such as tumours, asthma, and rheumatoid arthritis ( 21 ), although the medicinal value of these active ingredients has rarely been reported ( 30 ). SG is the dried S. scutellariae root from which baicalin is extracted from the by-product of Scutellaria flavones.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al ( 33 ) calculated the clinical cure rate of COVID-19 patients using a Chinese herbal formula containing Scutellaria and found that the clinical and fever symptom scores and inflammatory biomarkers were reduced. Ming et al ( 21 ) also found that Astragalus polysaccharides alleviated lipopolysaccharide-induced inflammatory lung injury by altering the intestinal microbiota in mice, while Li et al ( 31 ) reported that the flavonoid compound, kaverol, inhibits PRV replication in the brain, lungs, kidneys, heart, and spleen, alleviating pathological changes in these organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that anti-inflammatory activities of HAPS were more effective than those of APS ( 119 ). Furthermore, LPS-induced inflammatory lung injury mice orally administrated with 200 mg/kg APS for 14 consecutive days significantly reduced neutrophilic infiltration, phosphorylated NF-κB expression level and relative expressions of ICAM-1, Il-1β, Il-6, and TNF-α ( 120 ). Taken together, APS functions as an anti-inflammatory agent in animals and exerts its anti-inflammation mainly by inhibiting NF-κB signaling pathways and reducing expression of pro-inflammatory cytokines.…”
Section: Anti-inflammatory Properties Of Apsmentioning
confidence: 99%
“…Ming et al. ( 78 ) found that APS significantly increased serum concentrations of SCFAs, including butyric and propionic acids, by increasing the abundance of SCFA-producing genera such as Akkermansia , Coprococcus , and Oscillospira in the intestine. APS may control immune function by boosting cytokine release, promoting immune cell proliferation, and influencing immunoglobulin (Ig) production and immunological signaling ( 79 ).…”
Section: Mechanism Of the Active Ingredients Of Astragali Radix Membr...mentioning
confidence: 99%